PpMYB36 Encodes a MYB-Type Transcription Factor That Is Involved in Russet Skin Coloration in Pear (Pyrus pyrifolia) - Changqing Ma (Frontiers Media S.A., 2021)
Fruit color is one of the most important external qualities of pear (Pyrus pyrifolia) fruits. However, the mechanisms that control russet skin coloration in pear have not been well characterized. Here, we explored the molecular mechanisms that determine the russet skin trait in pear using the F1 population derived from a cross between russet skin (‘Niitaka’) and non-russet skin (‘Dangshansu’) cultivars. Pigment measurements indicated that the lignin content in the skin of the russet pear fruits was greater than that in the non-russet pear skin. Genetic analysis revealed that the phenotype of the russet skin pear is associated with an allele of the PpRus gene. Using bulked segregant analysis combined with the genome sequencing (BSA-seq), we identified two simple sequence repeat (SSR) marker loci linked with the russet-colored skin trait in pear. Linkage analysis showed that the PpRus locus maps to the scaffold NW_008988489.1: 53297-211921 on chromosome 8 in the pear genome. In the mapped region, the expression level of LOC103929640 was significantly increased in the russet skin pear and showed a correlation with the increase of lignin content during the ripening period. Genotyping results demonstrated that LOC103929640 encoding the transcription factor MYB36 is the causal gene for the russet skin trait in pear. Particularly, a W-box insertion at the PpMYB36 promoter of russet skin pears is essential for PpMYB36-mediated regulation of lignin accumulation and russet coloration in pear. Overall, these results show that PpMYB36 is involved in the regulation of russet skin trait in pear.